RAMIN BATANGK AND AMARE CULTURAL VALUES TOWARD ENGLISH LEARNING ACHIEVEMENT - Giovani, Wanda; Tawarik, Oxtapianus; Rufinus, Albert; Serli, Serli (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT This research investigates the influence of Dayak cultural values, specifically those inherent in the Ramin Batangk concept, on the English language achievements of students at Institut Shanti Bhuana in Bengkayang. The Ramin Batangk, a traditional Dayak longhouse, embodies a rich cultural heritage characterized by communal values such as cooperation, discipline, respect for nature, and spirituality. These values are integrated into the students' dormitory life, which reflects both traditional Dayak culture and modern boarding school practices. Employing a correlational research design, the study examines the relationship between students' perceptions of these cultural values and their English language performance. The findings indicate a positive correlation between the cultural values practiced within the dormitories and students' academic success in English. Specifically, values such as cooperation, discipline, and perseverance significantly contribute to enhancing students' English achievement. These results underscore the importance of a culturally enriched learning environment in fostering both academic success and the preservation of cultural identity. The study recommends that educational strategies at Institut Shanti Bhuana continue to emphasize the integration of Dayak cultural values to further promote academic excellence and personal development among students. ABSTRAK Penelitian ini mengkaji pengaruh nilai-nilai budaya Dayak, khususnya yang terkandung dalam konsep Ramin Batangk, terhadap pencapaian prestasi bahasa Inggris mahasiswa di Institut Shanti Bhuana Bengkayang. Ramin Batangk, sebuah rumah panjang tradisional Dayak, memuat warisan budaya yang kaya, ditandai dengan nilai-nilai kebersamaan seperti kerja sama, disiplin, penghormatan terhadap alam, dan spiritualitas. Nilai-nilai ini diintegrasikan dalam kehidupan asrama mahasiswa, yang mencerminkan perpaduan antara budaya Dayak tradisional dan praktik pendidikan asrama modern. Dengan menggunakan desain penelitian korelasional, studi ini meneliti hubungan antara persepsi mahasiswa terhadap nilai-nilai budaya tersebut dan pencapaian mereka dalam bahasa Inggris. Hasil penelitian menunjukkan adanya korelasi positif antara nilai-nilai budaya yang dipraktikkan di asrama dengan keberhasilan akademik mahasiswa dalam bahasa Inggris. Secara khusus, nilai-nilai seperti kerja sama, disiplin, dan ketekunan berkontribusi signifikan dalam meningkatkan prestasi bahasa Inggris mahasiswa. Temuan ini menekankan pentingnya lingkungan belajar yang kaya akan nilai budaya dalam mendukung keberhasilan akademik sekaligus pelestarian identitas budaya. Penelitian ini merekomendasikan agar strategi pendidikan di Institut Shanti Bhuana terus menekankan integrasi nilai-nilai budaya Dayak untuk semakin mendorong keunggulan akademik dan pengembangan pribadi mahasiswa.